1996
DOI: 10.1111/j.1460-9592.1996.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind comparison of morphine infusion and patient controlled analgesia in children

Abstract: The analgesia provided after major abdominal surgery in 30 children by continuous morphine infusion and patient controlled analgesia, also using morphine, was compared using a double-blind, double-dummy design. The groups of children were comparable in age, weight, duration of operation and sex ratio. Pain assessment was carried out by a single observer using a visual analogue scale and the Poker Chip Tool. Assessments took place during two four-hour periods, one on the day of operation and one the following d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Furthermore, patients in the PCA-group appeared to accept a pain score of 5.5 and did not titrate to achieve a pain-free state, while most health professionals titrate pain medication to reduce even mild pain. This was observed in previous studies in children as well as adults [25][26][27]. The analgesia-induced side effects, as perceived by the patient, may be an important reason for this phenomenon.…”
Section: Side Effects and Adverse Eventssupporting
confidence: 56%
“…Furthermore, patients in the PCA-group appeared to accept a pain score of 5.5 and did not titrate to achieve a pain-free state, while most health professionals titrate pain medication to reduce even mild pain. This was observed in previous studies in children as well as adults [25][26][27]. The analgesia-induced side effects, as perceived by the patient, may be an important reason for this phenomenon.…”
Section: Side Effects and Adverse Eventssupporting
confidence: 56%
“…However, after the study period, PCA has become increasingly common since it has been shown to have advantages compared with continuous morphine infusions in older children [20,21]. A PCA advantage is that the required amount of morphine generally is reduced which results in a reduced risk of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of PCA compared to conventional analgesic therapy includes high patient satisfaction with being able to control the pain themselves and the minimal delay between request for analgesia and pain relief [14]. Morphine is the analgesic opioid drug most frequently adopted in this practice [2,3,11,18] even if adverse effects such as nausea, vomiting, constipation, sedation, blood pressure instability, itching, allodynia and hyperalgesia may occur during treatment. Although several strategies may be employed when dealing with these adverse effects, they can be so severe that it is necessary to decrease or withdraw the morphine treatment causing the discomfort because of an inadequate pain management.…”
Section: Discussionmentioning
confidence: 99%